Boronic Acids and Beyond: ROS-Responsive Prodrugs as Tools for a Safer and More Effective Cancer Chemotherapy - Monteiro, Sofia A. G.; Gois, Pedro M. P.; António, João P. M. (Synlett, 2023)
Despite significant scientific advances and the wide variety of available treatments, cancer remains a major cause of death worldwide. Chemotherapy, which is frequently one of the first-line treatments, frequently suffers from low selectivity to cancer cells, leading to the appearance of important side effects. Thus, it becomes imperative to develop a new generation of targeted alternatives that spare the healthy tissues by delivering the cytotoxic payloads safely and selectively to cancer cells. In this respect, prodrugs that are activated by tumor-specific stimuli have attracted significant attention. Despite being a hallmark of cancer and present in high concentrations in cancer cells, reactive oxygen species (ROS) have been rather underexplored as a stimulus for the preparation of targeted prodrugs, particularly when compared with an acidic pH or glutathione. Despite their lower expression, ROS have recently been gaining substantial consideration, with various ROS-responsive prodrugs already reported with meaningful performances both in vitro and in vivo. This review aims to provide critical insights into this strategy by discussing the various available functional groups (with an important focus on boronic acids and their esters), their mechanisms of action, examples of their applications, advantages, limitations, and future challenges.1 Introduction2 Boronic Acids and Boronate Esters2.1 Histone Deacetylase Inhibitors2.2 DNA Alkylating Agents2.3 Selective Estrogen Receptor Modulators and Selective Estrogen Receptor Degraders2.4 ROS Inducers2.5 Prodrugs Based on Other Types of Anticancer Drugs3 Other ROS-Responsive Moieties3.1 Thiazolidinones3.2 1,3-Oxathiolanes3.3 Selenium Ethers3.4 Sulfur-Containing ROS-Responsive Moieties4 Summary and Future Perspectives
Keywords: boronic acids; cancer therapy; medicinal chemistry; reactive oxygen species; prodrugs; chemotherapy